2014
DOI: 10.1017/s0021859614000987
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of spent blewit mushroom compost andBacillus aryabhattaicombination on control of Pythium damping-off in cucumber

Abstract: SUMMARYPythium damping-off caused by Pythium aphanidermatum usually occurs in commercial nurseries of cucumber seedlings. The purpose of the present study was to develop a container medium for effectively suppressing Pythium damping-off of cucumber seedlings. Seven agricultural materials were tested for their suitability as substrates for the growth of cucumber seedlings. Bas Van Burren No. 4 peat moss (BVB) was able to promote the growth of cucumber seedlings, but it was ineffective against Pythium damping-of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…On the other hand, Firmicutes also increased following Streptomyces treatment, which is consistent with a previous study that the enhanced Firmicutes was also observed when the same Streptomyces treatment was applied on tomato [15]. The phylum Firmicutes comprises the class Bacillus, and the function of growth promotion and disease resistance has been reported in the genus Bacillus aryabhattai [37,38], Bacillus subtilis [39,40], and Bacillus amyloliquefaciens [41,42]. The enhancement of this phylum in the present study indicates that the stress resistance of the microbiota in the rhizosphere was enhanced by Streptomyces.…”
Section: Rhizosphere Microbiome Diversity and Structure Influenced By Streptomyces Applicationsupporting
confidence: 91%
“…On the other hand, Firmicutes also increased following Streptomyces treatment, which is consistent with a previous study that the enhanced Firmicutes was also observed when the same Streptomyces treatment was applied on tomato [15]. The phylum Firmicutes comprises the class Bacillus, and the function of growth promotion and disease resistance has been reported in the genus Bacillus aryabhattai [37,38], Bacillus subtilis [39,40], and Bacillus amyloliquefaciens [41,42]. The enhancement of this phylum in the present study indicates that the stress resistance of the microbiota in the rhizosphere was enhanced by Streptomyces.…”
Section: Rhizosphere Microbiome Diversity and Structure Influenced By Streptomyces Applicationsupporting
confidence: 91%
“…lycopersici and powdery mildew (Ding and Huang, 2017). A combination of spent blewit mushroom compost and B. aryabhattai has recently been shown to control Pythium damping-off in cucumber (Chen et al ., 2015). A B. mycoides strain isolated from the rice rhizosphere has recently been shown to produce biosurfactants, suppress the formation of zoospores by P. aphanidermatum and reduce damping-off by 35% in cucumber (Peng et al ., 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, SMC has been aroused as an alternative to the commercial peat substrate (Kandemir et al, 2009;Ünal, 2015;Zhang et al, 2012Zhang et al, , 2013. The use of SMC in the container substrate can efficiently inhibit the pathogen damage on horticultural crops (Segarra et al, 2007;Chen et al, 2015), promote nutrient uptake (Paredes et al, 2016;Sönmez et al, 2016), and promote crop growth (Ünal, 2015). However, the high pH value and electrical conductance (EC) prevent SMS to be used as the main component in the substrate (Szmidt and Chong, 1995;Gonani et al, 2011).…”
Section: Pepper Plant Culturementioning
confidence: 99%